2018
DOI: 10.35536/ljb.2018.v6.i2.a4
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance, Disclosure Quality, and Cost of Equity: Evidence from Pakistan

Abstract: The link between disclosure of corporate information and the cost of equity in firms is one of the most important issues in finance. This paper aims to examine the connection between corporate governance, disclosure quality of information, and the cost of equity in Pakistani-listed (PSX-listed) firms. Using the Generalized Methods of Movements (Sys-GMM) model, a sample of 167 non-financial firms listed on Pakistan Stock Exchange (PSX) for the period of 2011-2015was analyzed. Sys-GMM estimation was applied to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
2
9
0
2
Order By: Relevance
“…CEO tenure (TENURE) has a negative and insignificant association with the COE having a p-value of 0.000. However, the results are consistent with prior research work conducted in Pakistan by Hassan et al (2018) and Nosheen and Sajjad, 2018), by finding a negative association with the COE.…”
Section: Analysis and Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…CEO tenure (TENURE) has a negative and insignificant association with the COE having a p-value of 0.000. However, the results are consistent with prior research work conducted in Pakistan by Hassan et al (2018) and Nosheen and Sajjad, 2018), by finding a negative association with the COE.…”
Section: Analysis and Resultssupporting
confidence: 92%
“…Hence, H4 has not been accepted, although the sign is negative as hypothesized. However, the results are consistent with prior research work (Hassan et al, 2018;Nosheen and Sajjad, 2018), which also found a negative impact of board size on the COE.…”
Section: Analysis and Resultssupporting
confidence: 92%
See 3 more Smart Citations